Realising consilience: How better communication between archaeologists, historians and natural scientists can transform the study of past climate change in the Mediterranean. (15th March 2016) - Izdebski, Adam; Holmgren, Karin; Weiberg, Erika; Stocker, Sharon R.; Büntgen, Ulf; Florenzano, Assunta; Gogou, Alexandra; Leroy, Suzanne A.G.; Luterbacher, Jürg; Martrat, Belen; Masi, Alessia; Mercuri, Anna Maria; et al.
Abstract: This paper reviews the methodological and practical issues relevant to the ways in which natural scientists, historians and archaeologists may collaborate in the study of past climatic changes in the Mediterranean basin. We begin by discussing the methodologies of these three disciplines in the context of the consilience debate, that is, attempts to unify different research methodologies that address similar problems. We demonstrate that there are a number of similarities in the fundamental methodology between history, archaeology, and the natural sciences that deal with the past ("palaeoenvironmental sciences"), due to their common interest in studying societal and environmental phenomena that no longer exist. The three research traditions, for instance, employ specific narrative structures as a means of communicating research results. We thus present and compare the narratives characteristic of each discipline; in order to engage in fruitful interdisciplinary exchange, we must first understand how each deals with the societal impacts of climatic change. In the second part of the paper, we focus our discussion on the four major practical issues that hinder communication between the three disciplines. These include terminological misunderstandings, problems relevant to project design, divergences in publication cultures, and differing views on the impact of research. Among other recommendations, we suggest that scholars from the three disciplines should aim to create a joint publication culture, which should also appeal to a wider public, both inside and outside of academia. Graphical abstract: Highlights: We review methodological and practical aspects of interdisciplinary collaboration. We show how the use of narrative links the palaeosciences with the humanities. We analyse the disciplinary narratives of climate change and its societal impacts. We offer advice on project design integrating history, archaeology and the sciences. We discuss problems with disciplinary publication cultures and potential solutions.